Transcriptomic response of Sinorhizobium meliloti to the predatory attack of Myxococcus xanthus - Soto, María José; Pérez, Juana; Muñoz-Dorado, José; Contreras-Moreno, Francisco Javier; Moraleda-Muñoz, Aurelio (Frontiers in Microbiology, 2023)
Bacterial predation impacts microbial community structures, which can have both positive and negative effects on plant and animal health and on environmental sustainability. Myxococcus xanthus is an epibiotic soil predator with a broad range of prey, including Sinorhizobium meliloti, which establishes nitrogen-fixing symbiosis with legumes. During the M. xanthus-S. meliloti interaction, the predator must adapt its transcriptome to kill and lyse the target (predatosome), and the prey must orchestrate a transcriptional response (defensome) to protect itself against the biotic stress caused by the predatory attack. Here, we describe the transcriptional changes taking place in S. meliloti in response to myxobacterial predation. The results indicate that the predator induces massive changes in the prey transcriptome with up-regulation of protein synthesis and secretion, energy generation, and fatty acid (FA) synthesis, while down-regulating genes required for FA degradation and carbohydrate transport and metabolism. The reconstruction of up-regulated pathways suggests that S. meliloti modifies the cell envelop by increasing the production of different surface polysaccharides (SPSs) and membrane lipids. Besides the barrier role of SPSs, additional mechanisms involving the activity of efflux pumps and the peptide uptake transporter BacA, together with the production of H2O2 and formaldehyde have been unveiled. Also, the induction of the iron-uptake machinery in both predator and prey reflects a strong competition for this metal. With this research we complete the characterization of the complex transcriptional changes that occur during the M. xanthus-S. meliloti interaction, which can impact the establishment of beneficial symbiosis with legumes.